Electrical conductivity of ceramics based on (Cu1-x Agx)7SiS5I nanocrystalline powders - Studenyak Ihor; Студеняк Ігор; Bereznyuk Serhiy; Сергій Березнюк; Pogodin Artem; Погодін Артем; Filep Mykhailo; Філеп Михайло; Filep Mihály; Shender Iryna; Шендер Ірина; Oleksandr Kokhan; et al. (Sumy State University, 2020)
Abstract. Ceramic samples based on (Cu1-xAgx)7SiS5I nanocrystalline powders were manufactured by pressing them at ~ 400 MPa pressure and subsequent annealing at 973 K during 36 hours. Investigations of electrical conductivity of ceramics based on (Cu1-xAgx)7SiS5I solid solutions were carried out by the method of impedance spectroscopy in the frequency range from 10 Hz to 2×106 Hz and in the temperature range 292-383 K. It is established that with increasing the content of silver atoms in ceramic samples based on (Cu1-xAgx)7SiS5I, the ionic component of electrical conductivity increases nonlinearly, while electronic component decreases nonlinearly, and their ratio increases nonlinearly and for Ag7SiS5I exceeds 60000.
Keywords: solid solutions; ceramics; electrical conductivity; activation energy; compositional dependence